Evaluation of Local Government Innovation Program in Lampung Province (Jurnal Bina Praja, 2018)
The problem of public services capacity, such as budget, infrastructure, and social capital in regions, is a threat to the social conditions of the community if serious efforts are not anticipated by the local government. Therefore, it needs an alternative model as an option to address the problem of capacity. This study seeks to illustrate the efforts of new autonomous local governments in building public service capacity in new autonomous regions to identify the dynamics of sustainable public service capacity building in new autonomous regions and to design a model of the sustainable public service capacity building to strengthen the autonomous region. This model tries to achieve an intergenerational aspect of development. The research method used in this study is a qualitative approach that combines secondary data and primary data. Data were collected from three local governments with best practices in public service capacity management. The data were analyzed using an interactive model. The research showed that when the program capacity is well designed, it will produce good program sustainability capabilities as well, otherwise if the program capacity faces many obstacles and it will produce poor sustainability capabilities. The strengthening of innovative programs in the public service sector needs to adopt the role model of public sector innovation initiative. The model emphasizes the importance of identifying the role of innovation that is designed in a program to the real problems faced so that later public confidence about the urgency of innovation can be achieved.
Keywords: Program Innovation; Sustainability; Strengthening Roles; Local Government